1981
DOI: 10.1002/pssb.2221070154
|View full text |Cite
|
Sign up to set email alerts
|

Polarisabilities of ions in rutile (TiO2) calculated with Madelung potentials determined by Ewald's method

Abstract: We have been interested in why only materials with a high dielectric constant such as Ti02, W03, and H-Nb 0 are able t o make u s e of crystallographic s h e a r (CS) report /4/, t o clarify this question, we calculated, by using Madelung's method (i. e., direct summation), the Madelung potential at each site in rutile (Ti02) which was treated as an ionic crystal. Using the Madelung potential at 4+ the titanium site, we then determined the electronic polarisability of the T i ion following Ruffa' s theory /5/.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The large relaxation energy due to polarization in the formation of c.s. planes m ust be attributed to the large polarizabilities, especially the electronic polariz ability of the oxygen ion, as we have suggested in the past (Iguchi & Tilley 1977 a;Iguchi et al 1980Iguchi et al , 1981Iguchi et al , 1983. This leads to the contention th a t only mater with not only a high static dielectric constant, b u t also large refractive indices, such as Ti0 2, W 0 3 and H -N b 20 5 are able to make use of c.s.…”
Section: Relaxation Energymentioning
confidence: 86%
See 2 more Smart Citations
“…The large relaxation energy due to polarization in the formation of c.s. planes m ust be attributed to the large polarizabilities, especially the electronic polariz ability of the oxygen ion, as we have suggested in the past (Iguchi & Tilley 1977 a;Iguchi et al 1980Iguchi et al , 1981Iguchi et al , 1983. This leads to the contention th a t only mater with not only a high static dielectric constant, b u t also large refractive indices, such as Ti0 2, W 0 3 and H -N b 20 5 are able to make use of c.s.…”
Section: Relaxation Energymentioning
confidence: 86%
“…planes and polarizabilities in these materials was to be expected (Iguchi & Tilley 1977 a;Tilley 1977). F urther studies have suggested th a t an im portant feature in this respect is th a t crystals must show a large electronic polarizability for the oxygen ions (Iguchi et al 1980(Iguchi et al , 1981(Iguchi et al , 1983(Iguchi et al , 1984. Relaxation due to this polarizati is likely to have an im portant role to play in the formation and stabilization of c.s.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation